Meningkatkan Kinerja Guru dalam Menyusun dan Menyiapkan Administrasi Pembelajaran melalui Supervisi Akademik dengan Pendekatan Individual - Mohammadong Mohammadong (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to improve the performance of SMP Negeri 1 Puding Besar teachers in compiling and preparing learning planning administration. This research is a School Action Research (PTS) which was carried out in semester 2 of the 2019/2020 academic year with 20 teachers from SMP Negeri 1 Puding Besar. This research was conducted in 2 cycles, each cycle was carried out in stages; planning, action implementation, observation, and reflection. In cycle 1, the results obtained are very good and good categories have reached 85% or good categories and the average percentage per type of administration reaches 86%, good category (B). In cycle 2, the very good and good categories have reached 95% and the average percentage of teacher achievement per administrative type has reached 91%, or the very good category (A). Based on the results of interviews with teachers, they answered that supervision with an individual approach is very helpful because they can directly discuss and ask questions to improve performance and deficiencies according to the level of each teacher's shortcomings. Thus it can be concluded that academic supervision using an individual approach can improve the performance of SMP Negeri 1 Puding Besar teachers in preparing learning planning administration. Keywords: Academic Supervision, Individual Approach, Teacher Performance